Identification and control of unstable FOPTD processes with improved transients - S. Pandey; S. Majhi (Electronics Letters)
A set of explicit expressions for an accurate identification of unstable first order plus time delay (FOPTD) process using single relay feedback test are deduced. Thereafter, tuning rules for a feedforward and feedback combination of proportional‐integral and proportional controllers are proposed to enhance the closed loop transient performance. When the process output is distorted by measurement noise, a Fourier series based curve fitting technique is utilised for the reconstruction of true process output. Benchmark examples from literature are illustrated and thereafter comparisons are made to validate the effectiveness of the proposed identification and control scheme.